Frequency of Post-Operative Hematoma in Lumbar Disc Excision through Fenestration without Closed-Suction Drainage. Issue 1 (April 2016) - Umair, Muhammad; Bashir, Muhammad Farrukh Bashir; Aziz, Amer; Akram, Rizwan; Ahmad, Saeed
Introduction: Spinal epidural hematoma is a well-known complication of spinal surgery. To prevent hematoma formation its routine that suction drain is placed for 24 to 48 hours after laminectomy. But Clinically insignificant small epidural hematomas develop after Lumbar disc excision through interlaminar fenestration. The aim of this study is to find out Frequency of Post-Operative Hematoma in Lumbar Disc Excision through Fenestration without closed-suction drainage. Materials and Methods: This was a descriptive case series done at Ghurki trust teaching hospital Lahore from from January 2009 to January 2014. Total 423 cases who underwent Lumbar Disc Excision through Fenestration were included in the study. All the patients were followed for 7 days for postoperative Spinal Hematoma Formation which was considered positive in patients who either develop a new postoperative neurological deficit or pain and on mri shows Spinal Epidural Hematoma at the site of surgery. Results: Frequency of post-operative hematoma after lumbar disc excision through fenestration without using closed-suction drainage reveals 2.13%( n  = 9) while 97.87%( n  = 414) had no findings of hematoma. Conclusion: We concluded that frequency of post-operative hematoma after lumbar disc excision through fenestration without using closed-suction drainage is determined as insignificant.